Recognition Mechanism of a Novel Gabapentinoid Drug, Mirogabalin, for Recombinant Human α2δ1, a Voltage-Gated Calcium Channel Subunit. Issue 10 (15th May 2023) - Kozai, Daisuke; Numoto, Nobutaka; Nishikawa, Kouki; Kamegawa, Akiko; Kawasaki, Shohei; Hiroaki, Yoko; Irie, Katsumasa; Oshima, Atsunori; Hanzawa, Hiroyuki; Shimada, Kousei; Kitano, Yutaka; Fujiyoshi, Yoshinori
Graphical abstract: Highlights: Structural and ligand binding analyses of recombinant α2 δ1 reveal the binding mechanism of mirogabalin, a gabapentinoid drug. The importance of hydrophobic interactions between α2 δ1 and mirogabalin, and another α2 δ1 ligand, L-Leu, is newly identified. Unconserved residues of α2 δ1–4 at the α2 δ1/mirogabalin hydrophobic interaction site affect the ligand recognition specificity. Abstract: Mirogabalin is a novel gabapentinoid drug with a hydrophobic bicyclo substituent on the γ-aminobutyric acid moiety that targets the voltage-gated calcium channel subunit α2 δ1. Here, to reveal the mirogabalin recognition mechanisms of α2 δ1, we present structures of recombinant human α2 δ1 with and without mirogabalin analyzed by cryo-electron microscopy. These structures show the binding of mirogabalin to the previously reported gabapentinoid binding site, which is the extracellular dCache_1 domain containing a conserved amino acid binding motif. A slight conformational change occurs around the residues positioned close to the hydrophobic group of mirogabalin. Mutagenesis binding assays identified that residues in the hydrophobic interaction region, in addition to several amino acid binding motif residues around the amino and carboxyl groups of mirogabalin, are critical for mirogabalin binding. The A215L mutation introduced to decrease the hydrophobic pocket volume predictably suppressed mirogabalin binding and promoted the binding of another ligand, L-Leu, with a smaller hydrophobic substituent than mirogabalin. Alterations of residues in the hydrophobic interaction region of α2 δ1 to those of the α2 δ2, α2 δ3, and α2 δ4 isoforms, of which α2 δ3 and α2 δ4 are gabapentin-insensitive, suppressed the binding of mirogabalin. These results support the importance of hydrophobic interactions in α2 δ1 ligand recognition.